2023
DOI: 10.3389/fpsyg.2023.1149437
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the acculturation strategies of unaccompanied refugee minors in Germany

Maike Garbade,
Jenny Eglinsky,
Heinz Kindler
et al.

Abstract: BackgroundDifferent acculturation strategies might be related to different mental health outcomes and social participation of unaccompanied refugee minors (URMs), but little is known about which factors influence this acculturation process. Therefore, the aim of this investigation was to examine the impact of individual, stress-related, and contextual factors on the acculturation process of URMs in Germany.MethodsA sample of N = 132 URMs living in child and youth welfare service facilities in Germany completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Some studies reported immigrants adopted negative health practices such as less healthy diets and more sedentary lifestyles post migration (Bayog & Waters, 2018;Commodore-Mensah et al, 2018), although this is not always the case with some studies noting improved dietary practices and an increase in physical exercise (Basu & Insler, 2018;Li & Hummer, 2015). Although acculturation has been recognized as critical to the health outcomes of migrants, little is known about factors impacting this process (Garbade et al, 2023). This study suggests further research to understand the mechanisms involved in the process of acculturation among older Vietnam-born people.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported immigrants adopted negative health practices such as less healthy diets and more sedentary lifestyles post migration (Bayog & Waters, 2018;Commodore-Mensah et al, 2018), although this is not always the case with some studies noting improved dietary practices and an increase in physical exercise (Basu & Insler, 2018;Li & Hummer, 2015). Although acculturation has been recognized as critical to the health outcomes of migrants, little is known about factors impacting this process (Garbade et al, 2023). This study suggests further research to understand the mechanisms involved in the process of acculturation among older Vietnam-born people.…”
Section: Discussionmentioning
confidence: 99%